Does Whipworm Increase the Pathogenicity of Campylobacter jejuni? A Clinical Correlate of an Experimental Observation - Jennifer L Shin; Geoffrey W Gardiner; Wayne Deitel; Gabor Kandel (Canadian Journal of Gastroenterology)
Campylobacter jejuni is a leading cause of acute diarrhea worldwide, usually mild and self-limiting. No adequate hypothesis has yet been formulated to explain why in an otherwise healthy host this infection is occasionally severe. In a pig model, C jejuni has been shown to be pathogenic only in the presence of swine whipworm. A human case of life-threatening C jejuni colitis leading to toxic megacolon and acute renal failure, associated with concomitant whipworm (Trichuris suis) ova in the feces, is reported. The potential of T suis to potentiate C jejuni in humans deserves further study.